2002
DOI: 10.1002/ajmg.10467
|View full text |Cite
|
Sign up to set email alerts
|

Childhood‐onset ataxia: Testing for large CAG‐repeats in SCA2 and SCA7

Abstract: Infantile- and juvenile-onset spinal cerebellar ataxia (SCA) is associated with expansion of 130 to more than 200 CAG-repeats in the SCA2 and SCA7 genes. Routine clinical assays for SCA2 and SCA7, which use polymerase chain reaction (PCR) and denaturing PAGE (polyacrylamide gel electrophoresis), will not reliably detect such large expansions. An assay based on separation of PCR products on an agarose gel, blotting, and hybridization with a (CAG)6 oligonucleotide probe was used to test DNA from individuals more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 21 publications
(46 reference statements)
1
78
0
Order By: Relevance
“…While a recent study by Woodhead et al (2005) revealed that estimates of population differentiation based on EST-SSRs are comparable to those based on both anonymous SSRs and AFLPs in ferns, and large-scale comparative analyses suggest that only a very small percentage of all genes are experiencing positive selection (Tiffin and Hahn, 2002;Clark et al, 2003), some small fraction of all EST-SSRs will inevitably be subject to selection. Indeed, there are examples from the literature wherein certain genic SSRs are known to be associated with various diseases in animals (Zoghbi and Orr, 2000;Mao et al, 2002;Yamada et al, 2002) or pathogenicity/virulence in microbes (Peak et al, 1996;Grimwood et al, 2001). While more studies are needed before we will have a better understanding of the possible effects of genic SSRs in plants (Li et al, 2004), it seems safe to assume that at least a small percentage of loci will be evolving in a non-neutral manner.…”
Section: Jr Ellis and Jm Burkementioning
confidence: 99%
“…While a recent study by Woodhead et al (2005) revealed that estimates of population differentiation based on EST-SSRs are comparable to those based on both anonymous SSRs and AFLPs in ferns, and large-scale comparative analyses suggest that only a very small percentage of all genes are experiencing positive selection (Tiffin and Hahn, 2002;Clark et al, 2003), some small fraction of all EST-SSRs will inevitably be subject to selection. Indeed, there are examples from the literature wherein certain genic SSRs are known to be associated with various diseases in animals (Zoghbi and Orr, 2000;Mao et al, 2002;Yamada et al, 2002) or pathogenicity/virulence in microbes (Peak et al, 1996;Grimwood et al, 2001). While more studies are needed before we will have a better understanding of the possible effects of genic SSRs in plants (Li et al, 2004), it seems safe to assume that at least a small percentage of loci will be evolving in a non-neutral manner.…”
Section: Jr Ellis and Jm Burkementioning
confidence: 99%
“…6 Only few patients having 32 and 33 CAG repeats have been reported so far, with very late onset -between 50 and 60 years of age. 4,7,8 Extremely large expansions of 109, 200 and 500 CAG in infants have also been observed, [9][10][11] but are rarer.…”
Section: Spinocerebellar Ataxia Type 2 (Sca2) Is a Neurodegenerative mentioning
confidence: 99%
“…Death occurs early. Brain MRI showed extreme cerebellar and brainstem atrophy, but also different degrees of supratentorial atrophy and ventricular enlargement, and white matter signal abnormalities likely attributable to dysmyelination and/or delayed myelination 70, 71, 72, 73…”
Section: Infantile Formsmentioning
confidence: 99%